A Holistic Approach to the Measurement of Physical Function in Clinical Research - Jennifer C. Richards; Shelby L. Bachman; Krista Leonard-Corzo; Suvekshya Aryal; Jennifer M. Blankenship; Ieuan Clay; Kate Lyden (Digital Biomarkers)
Background: This commentary highlights the evolution of our understanding of physical function (PF) and key models/frameworks that have contributed to the current holistic understanding of PF, which encompasses not only a person’s performance but also the environment and any adaptations an individual utilizes. This commentary also addresses how digital health tools can facilitate and complement the assessment of holistic PF and enable both objective and subjective input from the participant in their real-world environment. Lastly, we discuss how successful implementation of digital tools within clinical research requires patient input. Summary: This commentary highlights how our understanding of PF has evolved to be more holistic. Key Messages: Inclusion of digital tools within clinical research can provide a path forward to holistically assess PF in a patient-focused manner. Background: This commentary highlights the evolution of our understanding of physical function (PF) and key models/frameworks that have contributed to the current holistic understanding of PF, which encompasses not only a person’s performance but also the environment and any adaptations an individual utilizes. This commentary also addresses how digital health tools can facilitate and complement the assessment of holistic PF and enable both objective and subjective input from the participant in their real-world environment. Lastly, we discuss how successful implementation of digital tools within clinical research requires patient input. Summary: This commentary highlights how our understanding of PF has evolved to be more holistic. Key Messages: Inclusion of digital tools within clinical research can provide a path forward to holistically assess PF in a patient-focused manner.